The mystery of the wild west bandit ebook - Warner, Gertrude Chandler (The Boxcar Children, 2014)
The Aldens are at Wildcat Crossing, a recreated frontier town full of cowboy fun! But when horses disappear and other pranks threaten to ruin the Wild West show, the Boxcar Children must find out who's the varmint causing all the trouble!